2019
DOI: 10.1007/s11577-019-00612-y
|View full text |Cite
|
Sign up to set email alerts
|

How Much Do Sources of Happiness Vary Across Countries? A Review of the Empirical Literature

Abstract: This article presents a review of empirical research exploring cross-national differences in the correlates of subjective well-being (SWB). I start by giving an overview of the concept of SWB across psychological, sociological, and economic literature. Measures of SWB have good cross-cultural validity, yet there is currently little consensus regarding the cultural universality of the definition of happiness. An overview of existing empirical literature points toward robust crossnational differences in mean lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 190 publications
(197 reference statements)
0
8
0
1
Order By: Relevance
“…Previous studies have also found cultural distinctions in predictors and consequences of happiness [ 16 ]. Self-esteem is often the strongest predictor of happiness in Western cultures, but this relationship is generally weaker in East Asian cultures [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also found cultural distinctions in predictors and consequences of happiness [ 16 ]. Self-esteem is often the strongest predictor of happiness in Western cultures, but this relationship is generally weaker in East Asian cultures [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subjective well-being is composed of a cognitive dimension: life satisfaction, and an affective dimension: positive and negative affects [13,14,15]. Both components are related to a variety of positive aspects relevant to adolescents’ lives, such as social support, self-esteem, self-efficacy, and optimism [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Because education opens up possibilities for not just material gain but also for enjoying life's experiences more fully, that it positively predicts life satisfaction is unsurprising. Finally, both being young and female matter significantly and positively for life satisfaction, two interesting results (Bonini, 2008;Stavrova, 2019).…”
Section: Post-materials Experiences and Life Satisfactionmentioning
confidence: 90%